PENGERUH MODAL KERJA TERHADAP PROFITABILITAS PADA INDUSTRI MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yuni Lestari; Lena Farida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to determine the effect of working capital on profitability in food and beverage industries listed in the Indonesia Stock Exchange (BEI) 2010-2014 study period. Working capital used as independent variables namely aks turnover, accounts receivable turnover and inventory turnover. While the dependent variable is used as a variable is return on equity in the food and beverage industry listed in Indonesia Stock Exchange (BEI). The method used to observe the effect of working capital on profitability is by using multiple linear regression.The data used in this research is secondary data, financial reports (annual report). As for the food and beverage industry data listed on the Stock Exchange over the five years 2010-2014. Sampling was done by sampling purposive sample used is 6 food and beverage industry companies. Classic assumption test in this study include normality test, multicollinearity, heterokedasitas test, autocorrelation test. Analysis of data using multiple linear regression analysis, t-test, f, and test the coefficient of determination. Analysis of data using multiple linear regression analysis with SPSS 21.The results showed that the variable cash turnover and accounts receivable turnover partially (t test) no significant effect on return on equity in the food and beverage industry listed in Indonesia Stock Exchange (BEI), while the variable inventory turnover is partially significant effect on return on equity the food and beverage industry listed in Indonesia Stock Exchange (BEI). The results of the study simultaneously (f test) showed a significant effect of the variable cash turnover, accounts receivable turnover and inventory turnover on return on equity in the food and beverage industry are listed on the Stock Exchange Industry (BEI).Keywords: Working capital, profitability, turnover Cash, Accounts Receivable Turnover, Inventory Turnover, Return on Equity